Improving Adherence to Essential Birth Practices Using the WHO Safe Childbirth Checklist With Peer Coaching: Experience From 60 Public Health Facilities in Uttar Pradesh, India - Marx Delaney, Megan (Glob Health Sci Pract, 2017)
BACKGROUND: Adherence to evidence-based essential birth practices is critical for improving health outcomes for mothers and newborns. The WHO Safe Childbirth Checklist (SCC) incorporates these practices, which occur during 4 critical pause points: on admission, before pushing (or cesarean delivery), soon after birth, and before discharge. A peer-coaching strategy to support consistent use of the SCC may be an effective approach to increase birth attendants' adherence to these practices. METHODS: We assessed data from 60 public health facilities in Uttar Pradesh, India, that received an 8-month staggered coaching intervention from December 2014 to September 2016 as part of the BetterBirth Trial, which is studying effectiveness of an SCC-centered intervention on maternal and neonatal harm. Nurse coaches recorded birth attendants' adherence to 39 essential birth practices. Practice adherence was calculated for each intervention month. After 2 months of coaching, a subsample of 15 facilities was selected for independent observation when the coach was not present. We compared adherence to the 18 practices recorded by both coaches and independent observers. RESULTS: Coaches observed birth attendants' behavior during 5,971 deliveries. By the final month of the intervention, 35 of 39 essential birth practices had achieved >90% adherence in the presence of a coach, compared with only 7 of 39 practices during the first month. Key behaviors with the greatest improvement included explanation of danger signs, temperature measurement, assessment of fetal heart sounds, initiation of skin-to-skin contact, and breastfeeding. Without a coach present, birth attendants' average adherence to practices and checklist use was 24 percentage points lower than when a coach was present (range: −1% to 62%). CONCLUSION: Implementation of the WHO Safe Childbirth Checklist with coaching improved uptake of and adherence to essential birth practices. Coordination and communication among facility staff, as well as behaviors with an immediate, tangible benefit, showed the greatest improvement. Difficult-to-perform behaviors and those with delayed or theoretical benefits were less likely to be sustained without a coach present. Coaching may be an important component in implementing the Safe Childbirth Checklist at scale. (After publication of this article, the impact results of the BetterBirth intervention were published in the New England Journal of Medicine [volume 377, pages 2313-2324, doi: 10.1056/NEJMoa1701075]. The results showed that the intervention had no significant effect on maternal or perinatal mortality or maternal morbidity, despite having positive effects on essential birth practices.)